To solve the equation \(-3x + 7 = 10\):
-
Subtract 7 from both sides: \[ -3x = 10 - 7 \] \[ -3x = 3 \]
-
Divide by -3: \[ x = -1 \]
Next, let's solve the equation \(3x - 9 = 0\):
-
Add 9 to both sides: \[ 3x = 9 \]
-
Divide by 3: \[ x = 3 \]
Now, combining the solutions from both equations, we have:
- From \(-3x + 7 = 10\), we get \(x = -1\).
- From \(3x - 9 = 0\), we get \(x = 3\).
Thus, the solution set is \({-1, 3}\).
The correct response is: \({−1, 3}\) (left brace negative 1 comma 3 right brace).